Pengembangan Kemampuan Berwudhu Anak Usia Dini Melalui Metode Bernyanyi di RA An-Najwan Bandar Lama Labuhan Batu Utara - Syahrizal Syahrizal; Suratno Suratno (EduInovasi: Journal of Basic Educational Studies, 2021)
This research is motivated by problems that are often encountered in the learning process related to how to present material to students effectively and efficiently regarding the development of the religious spirit of children, especially when learning the practice of ablution to early childhood. To be able to develop the ability to perform ablution in early childhood, appropriate and interesting methods are needed, one of which is the singing method. This method seeks to improve the accuracy, enthusiasm, and memory of children in performing ablution movements; and based on the results of observations at RA An-Najwan Bandar Lama Labuhan Batu Utara related to the love of children singing when performing ablution, it is one of the discussions that needs to be studied more deeply as a research material. Mansur (2005) said that the spirit of religion in early childhood can arise in two ways. First, a sense of dependence. Babies who are born are always dependent on others to meet their needs (protection, new experiences, getting feedback, and being known). Therefore, children's religion will be formed through various experiences received from the environment. Second, religious instincts. Every baby born already has religious instincts, but the child's religious behavior has not been seen. Therefore, educators should stimulate the religious development of children. Both the relationship between humans and God, as well as between humans and humans. This type of research is qualitative which is intended to describe and analyze phenomena, events, social activities, attitudes, perceptions, thoughts of people individually or in groups. The data collection procedure is by using the method of interview, observation, and documentation. To analyze the data, the researcher used three stages, namely, data reduction, data display and drawing conclusions. The results of research related to the development of early childhood ablution skills at RA An-Najwan Bandar Lama with the singing method were able to develop children's ablution skills effectively because children can see and do it directly through the singing method by demonstrating ablution activities. Keywords: Ability to perform ablution for early childhood, Singing method